Maritime security and the Blue Economy: intersections and interdependencies in the Indian Ocean. Issue 1 (2nd January 2018) - Voyer, Michelle; Schofield, Clive; Azmi, Kamal; Warner, Robin; McIlgorm, Alistair; Quirk, Genevieve
ABSTRACT: Maritime security is essential to supporting the Blue Economy. Many maritime security forums have been key supporters of the Blue Economy concept, particularly in the Indian Ocean region (IOR). This paper will explore the co-evolution and co-dependence of Blue Economy and maritime security agendas, with a particular focus on the IOR. It identifies two primary interactions between Blue Economy and maritime security interests. Firstly, maritime security is an enabler of the Blue Economy, for example, through safeguarding navigation routes, providing important oceanographic data to marine industries and protecting rights over valuable marine resources and activities within claimed zones of maritime jurisdiction. Secondly, an often overlooked role that maritime security plays in the Blue Economy is by being itself a source of economic development and growth. An expanded Blue Economy will create greater demand for maritime security capabilities, and this, in turn, will trigger increased investment and growth in these capabilities. The enhanced and increasingly diverse role that maritime security will continue to play in the Blue Economy can be seen across all sectors in the IOR.